Analysis of the Development of Potential Tourist Attractions to Increase Consumer Spending in Ranca Upas Bandung - Dian Sua Pratama, Bayu; Maryetti, Maryetti; Bobur, Sobirov (Riviera Publishing, 2022)
Introduction: Indonesia is a country with a distinctive variety of cultures and natural beauty and has the uniqueness of each region because that is why Indonesia is famous for its beautiful tourism potential, one of which is in Bandung. Bandung is a city of flowers and is famous for its natural panorama coupled with several tourism potentials in Bandung, especially at Ranca Upas. The purpose of this study is to find out what potential can be developed at Ranca Upas Bandung, what obstacles are faced by managers in developing the potential of Ranca Upas Bandung, and how to increase consumer spending at Ranca Upas Bandung, using the indicators of Feasibility of Ranca Upas Bandung Tourism Objects. Method: This research uses a descriptive qualitative method, and the research sampling technique uses purposive sampling, with the number of informants as many as six people. The data analysis technique used descriptive analysis. Result: Based on the results of identifying the potential of Ranca Upas Bandung, all the informants stated that the availability of public transportation had not been fulfilled, and the ancillary in terms of marketing was still not fulfilled. Then, tourist sources stated that onsen facilities were still not met and natural tourist attractions were not met. Conclusion: Maintain the beauty of nature, maintain cleanliness, and comfort in Ranca Upas Bandung. They are improving inadequate facilities and rethinking to find solutions for onsen so that visitors are interested in buying onsen entrance tickets. More actively promote Ranca Upas on social media, and collaborate with influencers so that more people are curious and visit Ranca Upas.